The new institutional economics of antitrust and regulation - Frank Bickenbach; Lars Kumkar; Rüdiger Soltwedel (Kiel Institute of World Economics (IfW), 1999)
Hybrid governance structures between markets and hierarchies in many industries, e.g., in energy and telecommunications, challenge antitrust and regulation policy. The paper focuses on the theoretical and methodological basis provided by the New Institutional Economics (NIE) for analyzing the economics of complex vertical and horizontal coordination problems. It sketches the specific view of NIE at industrial organization, antitrust and regulation, discusses three current issues – the European policy concerning complex vertical contracts, regulatory reform of the electricity industry and the allocation of regulatory competencies in the EU – and presents some implications of NIE for economic policy making, research and advisory activities.
Keywords: L51; L43; L42; L22; K23; D23; D72; H11; K21; 330; New institutional economics; antitrust; regulation; incomplete contracts; regulatory reform; economic models of federalism; Konzentrationspolitik; Theorie der Regulierung; Neue Institutionenökonomik; Industrieökonomik; Unvollständiger Vertrag; Theorie der Unternehmung; Business Network; Wettbewerbspolitik; Föderalismus; Netzzugang; Elektrizitätswirtschaft; Theorie; EU-Staaten